2012
DOI: 10.1590/s0100-736x2012001100012
|View full text |Cite
|
Sign up to set email alerts
|

Type C botulism in swine fed on restaurant waste

Abstract: This neurotoxin was present in food residues originating from restaurant and hotel kitchens, stored in barrels without shelter from the sun and administered in a collective trough without prior thermal treatment. Animals which died at different ages showed clinical signs of botulism characterized by ϐlaccid paralysis, weight loss, anorexia, weakness, lack of coordination, locomotion difϐiculties with the evolution of lateral recum bency with involuntary urination and defecation. No alterations were observed at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Concerns about the application of food waste recycling in poultry nutrition in the UK include the prevention of the spread of diseases such as avian influenza and Newcastle disease [63]. Furthermore, infectious organisms of public health significance that may be linked to feeding food waste to livestock include Salmonella, Campylobacter, Mycobacterium, Trichinella, Toxoplasma [56], and Clostridium [64]. Chemical hazards of food waste that are necessary to be assessed include antibiotics [65], mycotoxins, pesticides, and heavy metals, such as Pb, Cd, As, and Hg [28].…”
Section: Legal Framework Regarding Food Waste Utilization In Animal Feedmentioning
confidence: 99%
“…Concerns about the application of food waste recycling in poultry nutrition in the UK include the prevention of the spread of diseases such as avian influenza and Newcastle disease [63]. Furthermore, infectious organisms of public health significance that may be linked to feeding food waste to livestock include Salmonella, Campylobacter, Mycobacterium, Trichinella, Toxoplasma [56], and Clostridium [64]. Chemical hazards of food waste that are necessary to be assessed include antibiotics [65], mycotoxins, pesticides, and heavy metals, such as Pb, Cd, As, and Hg [28].…”
Section: Legal Framework Regarding Food Waste Utilization In Animal Feedmentioning
confidence: 99%
“…Antibodies, other variables, such as "Rural settlements or indigenous reservations", "Peri-urban areas or underserved communities", "Extensive pig farming", "Human food waste for animal feed", "Closeness to landfill sites", "Closeness to nature reserves", and "Contact with wild pigs", may not have a significant impact in this specific context. Nevertheless, our findings revealed that 29.79% (56/188) of properties in the study provided human food waste for pig feed, leading to significant health issues for the animals, such as type C botulism [52]. It is essential to note that the lack of significant differences among the variables tested in the univariate analysis does not necessarily indicate that these conditions are absent or do not play a role in the disease epidemiology.…”
Section: Discussionmentioning
confidence: 74%
“…Pantothenic acid deficiency affects the myelin sheath, while in Cu deficiency the lesion affects primary the axon and secondary the myelin sheath (De Lahunta & Glass 2009). Botulism causes flaccid paralysis and there are no gross or histologic lesions (Raymundo et al 2012). In rabies there is a non-suppurative encephalomyelitis associated with intracytoplasmatic inclusion bodies (Pessoa et al 2011).…”
Section: Discussionmentioning
confidence: 99%